Designing for online homework guidance - Hansen, Jens Jørgen; Remvig, Kirstin (Proceedings of the International Conference on Networked Learning, 2016)
This paper presents the preliminary research work on developing and conceptualizing methods and models for homework guidance and support of the training program offered by Homework Online (HO). The presented models are: Curriculum framework for homework guidance, Scenes of Guidance and Model of guidance methods. HO is an organisation led by State Library, Denmark wich operate a number of call centres for homework guidance in secondary education. The call centre offers guidance in an online environment. The concept of HO extend learning beyond the classroom and is an example of ‘networked learning’ where interactions between people are mediated by information/computertechnology (Goodyear & Carvalho, 2014). Our research utilise learning design as theory (Conole 2013) and Design Based Research (Gravenmeijer & Cobb 2006) as methodology to investigate: 1. What kind of learning design can contribute to develop HO’s training program? 2. In what way can new learning design contribute to the development of the tutors’ competences?